Training workshop on the basis of gymnastic qigoing as a factor of personal development of students with poor health - Kramida I. E. (Kharkov National Pedagogical University, 2013)
The aim is to study the effectiveness of the training of students of special medical group health program of the workshop and its change in the context of the students' positive personal qualities. A total of 282 participated relatively healthy 3 rd year student and more than 250 students of special medical group. Survey methods were used and statistical methods of data processing. It is proved that the lessons of the workshop on the basis of health qigong exercises are more effective in terms of personality development of students than the physical training for the relatively healthy students. It is proved that the development of positive personality traits of students increases with the duration of their training under the program of the workshop. It is shown that any of the workshop sessions on the basis of qigong exercises are an important factor in personal development of students with poor health.